The digestibility, ruminal fermentation and methane product of Cajanus cajan forage as a concentrate substitute in goats - Abidinsyah, D. A.; Suyub, I. B.; Jusoh, S.; Yaakub, H. (Diponegoro University, 2024)
Sixteen local goats (9.3 kg bodyweight) were assigned to different groups based on a 21-day com-pletely randomized design and fed with Cajanus cajan forage. The objectives of the study were to eval-uate digestibility, ruminal fermentation and estimation of methane production of C. cajan forage as a concentrate substitute in goats. Four treatments were used in the feeding trial: T0CC = 100% concen-trate; T25CC = 75% concentrate + 25% C. cajan forage; T75CC = 25% concentrate + 75% C. cajan forage; and T100CC = 100% C. cajan forage. Ruminal fluid was collected during the last week of the experiment after feeding and used to determine pH, ammonia, partial VFA, and methane gas produc-tion. Dry matter intake, nutrient digestibility, and total body weight gain were not significantly differ-ent (P>0.05) between goats fed with T0CC and T25CC. The addition of C. cajan forage to the diet did not significantly (P>0.05) affect pH, ammonia content, and total VFA but influenced acetate, propio-nate, butyrate, AP, and estimated CH4 produced. Hence, C. cajan forage may replace 25% of concen-trates in a rice straw-based diet for goats.